THE STATUS OF THE CHILD IN SOCIAL HOUSING. CASE STUDY OF ALI MENDJLI CITY, ALGERIA - Nerdjes Bennani; Samy Mezhoud (International Journal of Innovative Technologies in Social Science, 2024)
Algerian cities witnessed great developmental movements and major urban expansions that affected all sectors, so new residential areas with modern urban design and planning that differed from the traditional style known to it spread age. In this research, the diagnosis of the child's status within the new residential urban environments will be discussed. The research involves the case study of the town of Ali Mendjli in Algeria, through the neighborhood of a new social housing. The target is to highlight the child's status in this new urban environments, in order to build incubating cities for the child. In view of the importance of the child in the urban and social fabric and the influence that the city leaves on his personality, as essential part of the programmed plans for the state of Constantine, the study tries to answer several the questions in order to understand if the child environment is really taken into account during the planning process for the new housing. The results will be helpful for searching recommendations to the shortcomings that the new urban area suffers from, in terms of places designated for children there.